2007
DOI: 10.4049/jimmunol.179.1.590
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Enhance Dendritic Cell Response against Parasite Antigens via NKG2D Pathway

Abstract: Recent studies have shown that NK-dendritic cell (DC) interaction plays an important role in the induction of immune response against tumors and certain viruses. Although the effect of this interaction is bidirectional, the mechanism or molecules involved in this cross-talk have not been identified. In this study, we report that coculture with NK cells causes several fold increase in IL-12 production by Toxoplasma gondii lysate Ag-pulsed DC. This interaction also leads to stronger priming of Ag-specific CD8+ T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 43 publications
3
57
0
Order By: Relevance
“…Although the mechanisms or molecules involved in this DC-NK cell cross talk remain unclear, previous reports have suggested the participation of NKG2D in DC-NK cell responses to Toxoplasma gondii antigens (20) and the involvement of proteins of high-mobility group I in DC-ANK cell interaction (36). Another important finding in the present study is that while infection with L. amazonensis promastigotes …”
Section: Discussionsupporting
confidence: 65%
“…Although the mechanisms or molecules involved in this DC-NK cell cross talk remain unclear, previous reports have suggested the participation of NKG2D in DC-NK cell responses to Toxoplasma gondii antigens (20) and the involvement of proteins of high-mobility group I in DC-ANK cell interaction (36). Another important finding in the present study is that while infection with L. amazonensis promastigotes …”
Section: Discussionsupporting
confidence: 65%
“…Some recent studies have addressed the mechanisms by which NK cell might interact with DC (41)(42)(43). A recent study showed that NK cells can enhance the capacity of DC to present parasitic Ags via NKG2D receptor pathway (44). Using the NK-DC coculture approach, we demonstrated the direct influence of NK cells on DC FIGURE 8.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previously unappreciated role for NKG2D and its ligands in nonclassical NK T-cell-mediated immune responses has been revealed by using a transgenic mouse model of human hepatitis B infection (89). In addition, NKG2D-mediated interactions between NK cells and professional antigen-presenting cells have been shown to lead to stronger priming of antigen-specific CD8 ϩ T-cell responses by increasing interleukin-12 (IL-12) production from dendritic cells containing an antigen from Toxoplasma gondii lysate (36). Treatment of T. gondii-infected mice with anti-NKG2D antibody impaired the development of antigen-specific CD8 ϩ T cells, which led to a reduced ability to clear parasites from infected tissues.…”
Section: Discussionmentioning
confidence: 99%